EXPERIENCE OF EMERGENCY NURSE IN PERFORMING CARDIOPULMONARY RESUSCITATION (CPR) ON PATIENT WITH CARDIAC ARREST - Yundari, A.A Istri Dalem Hana; Darmika, I Gede Putu Yoga; Purwanti, Ika Setya (Jurnal Keperawatan Respati Yogyakarta, 2022)
Cardiac arrest is a leading cause of death in several countries, both inside and outside the hospital. About 295,000 people die in the USA due to sudden cardiac arrest and around 900 Americans die every day from cardiac arrest. The deaths that occur in the out of hospital and in of hospital areas and only 7% -8% survived (7). One of the causes of death is unable to handle rapidly and correctly, especially in implementation of Cardiac Pulmonary Resuscitation (CPR) as management of providing first aid and chain of survival. Based on phenomena occurs, nurses cannot perform their roles proper to standards frequently, this is illustrated when nurses are faced with patients with cardiac arrest in the Emergency Room (ER). The research is a qualitative phenomenological study using a phenomenological descriptive, conducted in the Emergency Room Installation Room (IGD) Sanglah Hospital Denpasar. It took six participants who determined by purposive sampling. Each participant was interviewed for 40–90 min uses interview guidelines, (filed note) and also Voice Recorder as research instrument. This study has five themes: (1). Understanding of emergency nurses about cardiac arrest, (2). Understanding of emergency nurses about cardiopulmonary resuscitation, (3). Experiences of emergency nurses in carrying out CPR in cardiac arrest patients, (4). Things that support emergency nurses in performing CPR in cardiac arrest patients, and (5). The obstacles that the emergency nurses found in doing CPR with theme limited man resources and facilities. Most of them described that the things that support emergency nurses in carrying out CPR on cardiac arrest patients are the resus call team, the existence of complete facilities and tools, and the existence of legal aspects and systems that support it. The obstacles felt by emergency nurses in conducting CPR on cardiac arrest patients resulted in sub-themes, limited human resources and limited facilities. Keywords: Emeregency Nursing; Cardiac Pulmonary Resuscitation (CPR);Cardiac Arrest